Improving Access to Care by Allowing Self-Referral to a Hepatitis C Clinic. (2009) - Doucette, Karen; Robson, Vicki; Shafran, Stephen; Kunimoto, Dennis
Abstract : BACKGROUND: Estimates suggest that more than 250, 000 Canadians are infected with hepatitis C virus (HCV), but less than 10% have been treated. Access to specialists in Canada is usually via health care professional (HCP) referral and, therefore, may be a barrier to HCV care. However, clinics that operate in conjunction with the Hepatitis Support Program, Edmonton, Alberta, allow self-referral. It is hypothesized that this improves access to care without increasing inappropriate referrals. OBJECTIVE: To compare the baseline characteristcs and outcomes of HCV patients who self-referred with those who were HCP-referred. METHODS: Data were collected from the Hepatitis Support Program HCV database and chart reviews. RESULTS: Between December 17, 2002, and December 31, 2007, 1563 patients were referred including 336 self- (21.5%) and 1227 HCP- referrals (78.5%). Self- and HCP-referred patients were similar in terms of age (mean [± SD] 43.0±10.3 years versus 43.9±10.0 years, respectively; P=0.18), sex (56.8% versus 62.0% [men], respectively; P=0.08) and risk factors for HCV (P=0.3), with 49.7% and 52.6%, respectively, identifying injection drug use as the primary risk factor. The two groups had similar HCV genotype distributions and liver biopsy fibrosis scores with similar treatment rates (31.3% versus 33.2%; P=0.6). Treatment outcomes were excellent (sustained virological response 40.2% for genotype 1, 67% for genotypes 2 and 3) in patients completing therapy and were similar between the two groups. Conclusion: Self-referred patients comprised 21.5% of patients accessing care in the clinic. Self- and HCP-referred patients had similar characteristics, treatment rates and outcomes. Facilitating self- referral to an HCV clinic can improve access to care, including risk reduction education and HCV treatment.